Quantifying the temporal variation of the contribution of fine sediment sources to sediment yields from Chilean forested catchments during harvesting operations - Schuller, Paulina; Walling, Desmond E.; Iroumé, Andrés; Quilodrán, César; Castillo, Alejandra (BOSQUE, 2021)
Fingerprinting techniques were incorporated into a paired catchment investigation in southern Chile to quantify the contribution of three fine sediment sources (catchment surfaces, forest roads and stream channels) to catchment suspended sediment yields during forest harvesting and replanting operations. Optimum composite fingerprints for use in sediment source discrimination and apportionment comprised 137Cs and 210Pbex for the control catchment (LUC) throughout the study and for the treatment catchment (LUT) during the pre-harvest period, and 137Cs and soil organic matter during harvest and post-harvest periods for LUT. Prior to harvesting, the dominant sediment source to the sediment load in both catchments was the stream channel and remained relatively constant throughout the study for LUC. For the entire study period the total suspended sediment yield from LUT (3,160 kg ha-1) approximately doubled that from LUC (1,650 kg ha-1). Most of this difference is accounted for by the increase in sediment output during the rainy months following clearcutting. The disturbance associated with forest operations in LUT caused the contributions to the load from the catchment slopes and forest roads to increase markedly (total contributions 835 and 795 kg ha-1, respectively). However, the total contribution from the stream channel for LUT during the study period (1,530 kg ha-1) remained similar to that from LUC. The results of the investigation demonstrated that any attempt to reduce sediment loading from forest harvesting would require adopting best management practices to reduce sediment mobilization from catchment surfaces and forest roads.